UPAYA PEMBERANTASAN TINDAK PIDANA PERJUDIAN OLEH KEPOLISIAN (STUDI KASUS POLRES TANAH KARO) - Annisa Claudia Br Regar; Rajin Sitepu (UNES Law Review, 2023)
The phenomenon of gambling is nothing new in people's lives, from the past until now the practice of gambling has existed. In essence, this gambling is contrary to religion and decency, it is very dangerous for the life of society, nation, and state. But in fact, gambling is growing rapidly and is increasingly being carried out, either clandestinely or transparently, in a simple way or in a modern way. So, the role of the police is needed in dealing with this one social problem. This study discusses gambling that is rife in the Tanah Karo area. The increase in gambling that occurs from year to year, why can there be an increase whether it is the lack of education received by the public or the lack of firmness of the police in handling criminal acts of gambling. So, this study aims to discuss how the efforts made by the police in eradicating gambling in Tanah Karo and what obstacles the police have in handling criminal acts of gambling. Based on the objectives to be achieved, this study uses an empirical juridical method which reveals laws and regulations related to legal theories which are the object of research. The results of this study reveal how the efforts made by the Tanah Karo Police in acting against criminal acts of gambling in Tanah Karo, have they been efficient in reducing gambling cases in Tanah Karo.